The Knowledge Economy and Lifelong Learning
XXI, 360 p.
Keywords: This book presents some of the most trenchant critical analyses of the widespread claims for the recent emergence of a knowledge economy and the attendant need for greater lifelong learning. The book contains two sections: first, general critiques of the limits of current notions of a knowledge economy and required adult learning, in terms of historical comparisons, socio-political construction and current empirical evidence; secondly, specific challenges to presumed relations between work requirements and learning through case studies in diverse current workplaces that document richer learning processes than knowledge economy advocates intimate. Many of the leading authors in the field are represented. There are no other books to date that both critically assess the limits of the notion of the knowledge economy and examine closely the relation of workplace restructuring to lifelong learning beyond the confines of formal higher education and related educational policies. This reader provides a distinctive overview for future studies of relations between work and learning in contemporary societies beyond caricatures of the knowledge economy. The book should be of interest to students following undergraduate or postgraduate courses in most social sciences and education, business and labour studies departments, as well as to policy makers and the general public concerned about economic change and lifelong learning issues. D. W. Livingstone is Canada Research Chair in Lifelong Learning and Work and Professor Emeritus at the Ontario Institute for Studies in Education, University of Toronto. David Guile is Professor of Education and Work at the Institute of Education, University of London.